MODEL PEMBELAJARAN MULTILITERASI BERBANTUAN MEDIA BIG BOOK TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA DI KELAS V SEKOLAH DASAR - Agung Pramujiono; Dudu Suhandi Saputra; Reza Rachmadtullah (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2020)
This study aims to determine the effectiveness of the use of multiliteration learning models assisted by big book media in improving the reading comprehension skills of students in grade V of elementary school. This research is an experimental study with the research design used in this study, namely Pretest Posttest Control Group Design. The data analysis technique in this study was the T-test. The results showed that based on the results of the different test with independent samples test, it was known that the Sig (2- tailed) value was 0.00 less than 0.05 thus it could be concluded that there were differences which are signed between the average reading comprehension of students in the experimental class with the group of students in the control class. The average score in the experimental class was 63.39, with a maximum value of 89.66 and a minimum value of 31.03. Meanwhile, the average score in the control class was 39.71 with a maximum value of 68.57 and a minimum value of 38.10. In general, it can be concluded that in improving reading comprehension skills in grade V elementary schools can be using multiliteration learning models assisted by big book media.